Medidas de esperança, religiosidade, personalidade e uso de drogas em adolescentes - Moraes, Allana Almeida (2017)
Research in Positive Psychology highlights that human forces, such as hope, operate as shock absorbers against mental illness, being determinant for positive youth development. Therefore, the general objective of this dissertation was to explore “hope” during adolescence. Thus, two studies, a theoretical and an empirical, were conducted in the form of articles. The theoretical article sought, from a systematic review of the literature, to contemplate a general panorama regarding the studies involving the construction of hope in adolescence, aiming to reflect about scientific productions in this area. The studies included in the review englobe the relationship of hope with others constructs, in different countries. The data found point to empirical proposals associating hope with essential virtues for good youth development, demonstrating that this is a promising area for the performance of psychology in Brazil. The empirical article aimed to identify characteristics of hope, religiosity and personality and its relation with drug use in a sample of 668 school adolescents, from 14 to 18 years old, attending to the 8th grade and 9th grade of elementary school and the 3 years of high school in Public schools in a metropolitan city in the southern region of the country. All participants answered a sociodemographic data questionnaire, the Dispositional Scale of Hope, the Duke-Durel Religious Accuracy Scale (P-DUREL), the Drug Use Screening Inventory (DUSI-R), and the Temperament and Character Inventory (TCI). It was found that higher levels of hope are associated with greater non-organizational religiosity and non-use of alcohol. Regarding personality, higher levels of hope was associated with the dimensions of the Self-directedness, Cooperativeness, and Self-Transcendence character. When assessing the final model, hope in adolescents who didn’t use alcohol was better explained by non-organizational religiosity and the personality dimentions Harm Avoidance, Novelty Seeking and Persistence. The findings reveal the importance of studies addressing protective factors for substance use during adolescence, since that period is characterized by exposure and vulnerability to offers and alcohol and other drugs use.